Perovskite Lenses: Flat Lenses Based on 2D Perovskite Nanosheets (Adv. Mater. 30/2020). Issue 30 (28th July 2020) - Wang, Ziyu; Yang, Tieshan; Zhang, Yupeng; Ou, Qingdong; Lin, Han; Zhang, Qianhui; Chen, Huanyang; Hoh, Hui Ying; Jia, Baohua; Bao, Qiaoliang
Abstract : In article number 2001388, Yupeng Zhang, Baohua Jia, Qiaoliang Bao, and co‐workers develop flat lenses based on 2D perovskite nanosheets using a cost‐effective mask‐free femtosecond direct laser writing system. The tunable material property affords effective manipulation of both amplitude and phase of the incident light, which is focused into a subwavelength 3D spot with a resolution in the range of 0.5‐0.9λ.